Fatigue characteristics of 6061 aluminum alloy subject to 3.5% NaCl environment - Chanyathunyaroj, Kittisak; Phetchcrai, Sompob; Laungsopapun, Ghit; Rengsomboon, Amornsak (International journal of fatigue, 2020)
•Observed the rotating bending fatigue in 3.5% NaCl environment.•The fatigue life decreased over 51 times by 3.5% NaCl Solution.•The 3.5% NaCl Solution shorten the fatigue life from several days to a few hours.•The 3.5%NaCl solution causes corrosion pits on the surface leading to crack nucleation sites. The rotating bending fatigue life of extruded 6061 aluminum alloy in a 3.5% NaCl environment was studied. It was found that under this environment solution fatigue life was significantly reduced by over 51 times, the fatigue life being shortened from several days to a few hours. Moreover, fatigue under the 3.5% NaCl solution could remove the endurance limit. The solution promoted the generation of many tiny pits, which were created rapidly on the surface of the specimens. These pits acted as crack nucleation sites leading to fatigue failure. The results indicate that pitting corrosion can markedly decrease the fatigue life.